Control of Rhipicephalus (Boophilus) microplus (Acari: Ixodidae) with vegetable extracts - BROGLIO-MICHELETTI, SÔNIA MARIA FORTI; NEVES-VALENTE, ELLEN CARINE; ALVES DE SOUZA, LEILIANNE; DA SILVA-DIAS, NIVIA; GIRÓN-PÉREZ, KATHERINE; PRÉDES-TRINDADE, ROSEANE CRISTINA (Revista Colombiana de Entomología, 2009)
The efficacy of various plant extracts in the control of Rhipicephalus (Boophilus) microplus was evaluated in the laboratory. Engorged females were collected from cattle and were isolated in Petri dishes. Organic alcoholic extracts at 1% (weight/volume) were used from seeds of Annona muricata (Annonaceae), flowers of Syzygium malaccensis (Myrtaceae), leaves of Cymbopogon citratus (Poaceae), leaves of Azadirachta indica (Meliaceae) and hexane extract 1% (weight/volume) of A. indica seeds. The control groups consisted of females either untreated or treated with distilled and sterile water and dimethylsulfoxide (DMSO) at a concentration of 1%. The extract of A. muricata seeds showed the highest acaricide power, with 100% efficacy, followed by flower extracts of S. malaccensis (75% and 57.25%) and seeds of A. indica (65% and 38.50%). There was a 100% reduction in the eclosion of larvae from eggs of females treated with the seed extract of A. muricata.